Economic possibilities for our grandchildren: 90 years later - Jörg Bibow (Levy Economics Institute of Bard College, 2024)
This paper revisits Keynes's (1930) essay titled "The economic possibilities for our grandchildren." We discuss the three broader trends identified by Keynes that he expected would come to characterize the socio-economic evolution of advanced countries under individualistic capitalism: first, continued technological progress and capital accumulation as the main drivers of exponential growth in economic possibilities; second, a gradual general rebalancing of life choices away from work; and third, a change in the code of morals in societies approaching an envisioned stationary state of zero net capital accumulation in which mankind has solved its economic problem and enjoys a lifestyle predominantly framed by leisure rather than disutilityyielding work. We assess actual outcomes by 2023 and attempt to peek into the future economic possibilities for this generation's grandchildren.
Keywords: B22; B31; E20; J22; N10; Q40; 330; Keynes; technology; growth; work; leisure; capitalism